A Comprehensive Analysis of Partial Shading Effect on Output Parameters of a Grid-connected PV System - H. Rahimi Mirazizi; M. A. Shafiyi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
One of the issues of grid-connected photovoltaic systems is the effect of the partial shading on the key parameters and performance of the system. In practice, a share of the entire PV panel may shadded because of the various reasons, inevitably. In this case, the key parameters of the system output are affected with respect to the shading extent and paradigm. In this paper, the effects of the various partial shading patterns on the ouput of the system are examined. This is performed by deriving relevant equations and appropriate modeling of the system and defining different scenarios. The analysis on the system performance is carried out on the dominant output parameters including panel voltage, panel power, and total harmonic distortion (THD) of the inverter. Also, the study considers the effect of using bypass diodes in the panels or not. Addintionally, to compare derived conclusions, the study is implementd on a practical system. The set up is made up of a 7-level multi-level inverter, a Z-source converter, and 1 kW lateral circuitry. The real world test results of the study demonstrate a negligible deviation compared to the simulation results.